Visceral larva migrans detection using PCR–RFLP in BALB/c mice infected with Toxocara canis. (2020) - Özbakış, G.; Doğanay, A.
Abstract: Toxocara canis is an important zoonotic roundworm distributed worldwide. The infective larvae of T. canis are one of the causes of visceral larva migrans (VLM), a clinical syndrome in humans. Diagnosing VLM is difficult, and the differential diagnosis of the larval development stage is limited. Therefore, this experimental research aimed to diagnose T. canis larvae using a molecular method, not only in liver tissue, which is the most commonly affected tissue, but also in the limb muscles, lungs and brain tissues. For this purpose, 24 BALB/c mice were infected with 1000 embryonated T. canis eggs. Necropsies were performed on the second, fourth, seventh and 14th days post-infection. While a part of the samples were digested with pepsin-HCl, the molecular method was used for the remainder of the samples to replicate the mitochondrial DNA adenosine triphosphate (ATP) synthase subunit-6 gene region of T. canis . BbsI, a restriction endonuclease, was used to determine the specificity of the amplicons obtained from Polymerase chain reaction (PCR). The detection limit for embryonated eggs was recorded. The PCR results showed that the sensitivity of the PCR analysis was 83.3% in the liver (with 88.8% accuracy), 87.5% in the lungs (with 91.6% accuracy) and 75.0% in the brain, forelimb and hindlimb muscles (with 83.3% accuracy). In all tissues, the test specificity was determined to be 100%. In this study, the molecular method was applied to only experimentally infected BALB/c mice tissues; thus, it is suggested that it can be also employed in different paratenic hosts and materials possibly infected with T. canis .